136k views
3 votes
Please help

Be sure to show your work and solve for f:
8 = f (13-2)

2 Answers

3 votes

Answer:

Simplifying

8 = F + -1(13 + -2)

Combine like terms: 13 + -2 = 11

8 = F + -1(11)

Multiply -1 * 11

8 = F + -11

Reorder the terms:

8 = -11 + F

Solving

8 = -11 + F

Solving for variable 'F'.

Move all terms containing F to the left, all other terms to the right.

Add '-1F' to each side of the equation.

8 + -1F = -11 + F + -1F

Combine like terms: F + -1F = 0

8 + -1F = -11 + 0

8 + -1F = -11

Add '-8' to each side of the equation.

8 + -8 + -1F = -11 + -8

Combine like terms: 8 + -8 = 0

0 + -1F = -11 + -8

-1F = -11 + -8

Combine like terms: -11 + -8 = -19

-1F = -19

Divide each side by '-1'.

F = 19

Simplifying

F = 19

User Ecarrion
by
5.4k points
3 votes

Answer:

8 = f (13-2)

8=13f-2f

8=11f

8 / 11 = 11f / 11

8/11=f

f=8/11

Explanation:

User Neumann
by
5.1k points